PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN BIAYA OPERASIONAL TERHADAP PAJAK PENGHASILAN BADAN TERUTANG PADA PERUSAHAAN SEKTOR INDUSTRIBARANG KONSUMSI DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Sembiring, Yan Christin Br; Ginting, Raumi Julita Br; Sitanggang, Abdonsius (UNIKA Santo Thomas, 2024)
This study aims to examine the effect of Longterm Debt to Asset Ratio (LDAR), Debt to Equity Ratio (DER), profitability and operating costs on corporate income tax payable partially and simultaneously. The population in this study, consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2018-2022 with a population of 63 companies. The number of samples was 11 companies in the 5-year research period with 55 observations. Sampling using purposive sampling technique. The analysis method used is descriptive statistical test, classical assumption test which includes normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. Using multiple linear regression analysis, hypothesis testing, and determination test using SPSS version 25 to process data. The results of this study indicate that LDAR partially has a negative and significant effect on corporate income tax payable, and DER, profitability, and operational costs partially have a positive and significant effect on corporate income tax payable, while simultaneously LDAR, DER, profitability, and operational costs have a positive and significant effect on corporate income tax payable in consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2018-2022.